Assessment of chronic limb threatening ischemia using thermal imaging. (February 2023) - Pakarinen, Tomppa; Joutsen, Atte; Oksala, Niku; Vehkaoja, Antti
Abstract: Objectives: Current chronic limb threatening ischemia (CLTI) diagnostics require expensive equipment, using ionizing radiation or contrast agents, or summative surrogate methods lacking in spatial information. Our aim is to develop and improve contactless, non-ionizing and cost-effective diagnostic methods for CLTI assessment with high spatial accuracy by utilizing dynamic thermal imaging and the angiosome concept. Approach: Dynamic thermal imaging test protocol was suggested and implemented with a number of computational parameters. Pilot data was measured from 3 healthy young subjects, 4 peripheral artery disease (PAD) patients and 4 CLTI patients. The protocol consists of clinical reference measurements, including ankle- and toe-brachial indices (ABI, TBI), and a modified patient bed for hydrostatic and thermal modulation tests. The data was analyzed using bivariate correlation. Results: The thermal recovery time constant was on average higher for the PAD (88%) and CLTI (83%) groups with respect to the healthy young subjects. The contralateral symmetry was high for the healthy young group and low for the CLTI group. The recovery time constants showed high negative correlation to TBI ( ρ = -0.73 ) and ABI ( ρ = -0.60 ). The relation of these clinical parameters to the hydrostatic response and absolute temperatures (| ρ|<0.3 ) remained unclear. Conclusion: The lack of correlation for absolute temperatures or their contralateral differences with the clinical status, ABI and TBI disputes their use in CLTI diagnostics. Thermal modulation tests tend to augment the signs of thermoregulation deficiencies and accordingly high correlations were found with all reference metrics. The method is promising for establishing the connection between impaired perfusion and thermography. The hydrostatic modulation test requires more research with stricter test conditions. Highlights: Thermal modulation test increases the diagnostic possibilities for PAD. Thermal recovery time shows high correlation with clinical reference measurements. Absolute temperature may be a poor metric for PAD diagnostics. Contralateral limb thermal comparison could reveal PAD lesions.